Cellular and molecular basis of haploidentical hematopoietic stem cell transplantation in the successful treatment of high-risk leukemias: role of alloreactive NK cells - LOCATELLI, FRANCO; PENDE, DANIELA; MINGARI, MARIA C.; BERTAINA, ALICE; FALCO, MICHELA; MORETTA, ALESSANDRO; MORETTA, LORENZO (Frontiers in Immunology, 2013)
Natural Killer (NK) cells are involved in innate immune responses and play a major role in tumor surveillance and in defence against viruses. Human NK cells recognize HLA-class I molecules via surface receptors (KIR and NKG2A) delivering signals that inhibit NK cell function and kill HLA-class I-deficient target cells, a frequent event in tumors or virus-infected cells. NK cell triggering is mediated by activating receptors that recognize ligands expressed primarily on tumors or virus-infected cells. NK cells play also a key role in the cure of high-risk leukemias. Thus, donor-derived “alloreactive” NK cells are fundamental effectors in adult acute myeloid leukemia (AML) and in pediatric acute lymphoblastic leukemia (ALL) patients undergoing haploidentical hematopoietic stem cell transplantation (HSCT). Alloreactive NK cells mediate killing of leukemia cells and patient’s DC, thus preventing respectively leukemic relapses and graft-versus-host responses. FACS analysis of KIRs expressed by NK cells allows to define the size of the alloreactive NK subset and the selection of the best potential donor. Recently, it has been shown that also the expression of activating KIRs, in particular the (C2-specific) KIR2DS1, may contribute to donor NK alloreactivity. It has also been established a correlation between the size of the alloreactive NK cell population and the clinical outcome. Notably, the alloreactive NK cells derived from donor’s HSC are generated and persist in patients over time. The high survival rates of patients undergoing haploidentical HSCT highlight an important new reality in the setting of allograft performed to cure otherwise fatal leukemias. Novel approaches are in progress to further improve the clinical outcome based on the infusion of donor alloreactive NK cells either as a component of the transplanted cell population or as in vitro expanded NK cells.